Treatment Outcome of Childhood Hodgkin Lymphoma after Chemotherapy Alone (Medical Forum Monthly, 2024)
Objective: To find the outcome of Hodgkin lymphoma treatment in children without radiotherapy using chemotherapy as a single treatment modality. Study Design: Descriptive retrospective study. Place and Duration of the Study: This study was conducted at the Pediatric Oncology Department, Children’s Hospital & Institute of Child Health, Multan from January, 2006 to January, 2014.Materials and Methods: All newly diagnosed children with Hodgkin lymphoma up to the age of 15 years were included in the study. Diagnosis was made on history, clinical examination and lymph node biopsy for histopathology & immunohistochemical staining. X-Ray chest, CT scan of the abdomen, bone scan and bone marrow biopsy were done for staging the disease. Chemotherapy was given to all children according to UKCCSG (United Kingdom Childhood Cancer Study Group) protocol for treatment of Hodgkin lymphoma. Response to treatment was noted after completion of chemotherapy.Results: Among 60 children with Hodgkin lymphoma, 55(92%) were male with M: F = 11.5:1.Age range at presentation was 3.5-15 years with mean of 8.5 years. Cervical lymphadenopathy was noted in 52(87%) & mediastinal lymphadenopathy in 8(13%) patients. Stage I, II, III & IV were found in 13(22%), 4(7%), 34(56%) & 9(15%) respectively. Mixed cellularity (MC) was the most common histopathological type, found in 43(72%) patients, followed by nodular sclerosis(NS) in 13(22%) and lymphocyte predominant (LP) in 3(5%).Lymphocyte depleted(LD) type was found in only one patient. On immunohistochemical staining CD30 was positive in all patients. So far, 53 (88%) children have completed their treatment and showed complete response to chemotherapy alone, 4(7%) got relapse & 3(5%) expired during treatment.Conclusion: Most of the children with Hodgkin lymphoma show complete response to the chemotherapy alone and can be treated without radiotherapy. However more patients and long-term follow up is needed for making definite conclusions